Assessment of major reproductive problems of dairy cattle in selected sites of central Zone of Tigrai Region, northern Ethiopia - Weldegebriall, B. (Mekelle University, 2015)
A cross sectional study to identify the prevalence of major reproductive problems ofdairy cattle and the possible risk factors in selected sites of Central zone of Tigrai Regionfrom September 2014 to April 2015 was conducted. In this study a total of 120respondents were interviewed and the finding revealed that the most frequentlyencountered reproductive health problems are repeat breeding, anoestrus, retained fetalmembranes, abortion, uterine prolapsed, and testicular swelling as responded by 26.7%,20.0%, 5.8%, 5.8%, 28.3%, and 26.7% of the interviewee. Similarly a record of 265 dairycows was examined to determine the reproductive problems of dairy cattle and associatedrisk factors and the finding indicated that 19.3% of the cattle have reproductive problems.The major reproductive problems found were 9.1% repeat breeding, 4.2% anoestrus,3.8% abortion, 1.1% RFM, 0.8% pyometra and 0.4% uterine prolapse. In addition, a totalof 414 blood samples for sera were collected from both sexes and greater than 6 monthsage to determine sero-prevalence and associated risk factors of bovine brucellosis in thestudy area. The Rose Bengal Plate Test (RBPT) was used on sera as a screening test forbrucellosis. The prevalence of bovine brucellosis found was 0.0%. Analysis of riskfactors of major reproductive problems from the retrospective study showed that exceptin the case of sanitation and pregnancy status, the overall prevalence of reproductiveproblems were significantly (p<0.05) influenced by breed, location, lactation status,production system, age, parity, body condition score, herd type, herd size and housingsystem. Generally the current finding revealed that reproductive health problemscommonly exist in the study area through their percentage and types vary from time totime; hence, regular reproductive health management and proper formulation of rationcould be the possible solutions to alleviate the problems encountered in differentproduction systems.